Effectiveness of educational interventions to raise men's awareness of bladder and bowel health: a systematic review - Hodgkinson, B.; Tuckett, A.; Hegney, Desley; Paterson, J.; Kralik, D. (University of Adelaide, 2010)
Background: Urinary incontinence (UI) has been defined as a condition in which the involuntary loss of urine is a social or hygienic problem and is objectively demonstrable. Urinary incontinence is a common health problem that carries with it significant medical, psychosocial and economic burdens. Fecal incontinence has been defined as the involuntary or inappropriate passing of liquid or solid stool and can also include the incontinence of flatus. Studies suggest that twice as many men suffer from fecal incontinence compared to urinary incontinence whilst more than three times as many women suffer from urinary incontinence compared to fecal incontinence. The general consensus in the literature is that barriers exist for seeking help for those with incontinence. Review question: ‘How effective are educational interventions at raising men’s awareness of bladder and bowel health?’ Types of participants: Adult and adolescent males (age 12 years and over). Types of interventions: Any intervention, program or action that provided information, or attempted to raise awareness of men’s bladder and bowel health. Types of outcome measures: The primary outcomes of interest included any measure defined by included studies such as: bladder and bowel management and treatment; increased knowledge of bladder and bowel health; number of attendees at promotion. Types of studies: As this review attempted to evaluate the effectiveness of an intervention or interventions, reviewers considered studies using concurrent controls. Search strategy: The search strategy was designed to identify both published and unpublished material and was restricted to English language publications with a publication date of 10 years prior to the search with the exception of a review of seminal papers before this time.Assessment of methodological quality: The quality of included studies was assessed by two reviewers using the Joanna Briggs Institute Checklists for experimental and observational studies. Data extraction: For each included paper the type of information that was extracted and tabulated in a database followed the JBI Data Extraction Form for Experimental and Observational Studies. Data synthesis: Where possible relative risk (RR), odds ratios (OR), Mean differences and associated 95% confidence intervals (95% CI) were calculated from individual studies. For homogeneous studies quantitative results were combined into a meta-analysis for evaluation of the overall effect of an intervention. Where heterogeneity existed between studies the results were presented in a narrative summary. Review results: Description of studies - The review identified 12 RCT and 2 controlled trials. Ten studies evaluated the effectiveness of interventions on the incidence of urinary incontinence symptoms in men after prostatectomy. Only two trials examined interventions to manage post-micturition dribble, one evaluated the effectiveness of lifestyle and behavioural modifications to manage lower urinary tract symptoms and one evaluated the use of a consensus guideline for the management of continence by primary health care teams in an urban general practice. No controlled trials evaluated interventions to improve men’s knowledge or management of bowel health, or to improve men’s attendance at promotional events. Methodological quality - Few of the RCT described the method of randomisation and no trials reported using blinding either to assessment or to treatment. Two studies did not provide the measures of dispersion (no standard deviation), one study provided graphical data only and one presented no data whatsoever.Results: Pelvic floor muscle exercises with or without additional interventions are effective at reducing the incidence of urinary incontinence in men >65 years who have had a prostatectomy. Education on lifestyle and behavioural modifications may be more effective in reducing lower urinary tract symptoms than doing nothing. Pelvic floor muscle exercises may be effective in treating post-micturition dribble in men with or without erectile dysfunction. Providing verbal feedback to participants to support pelvic floor muscle exercises technique appears to be as effective as biofeedback for improvement of urinary incontinence symptoms in this group. No evidence for the effectiveness of education interventions on faecal incontinence. No evidence for the effectiveness of education interventions to improve men’s attendance at promotional events. Discussion: The results of this review have highlighted that with the exception of pelvic floor muscle exercises (PME) after prostatectomy, few controlled trials have examined the effectiveness of any interventions at raising awareness of bladder and bowel health in males aged 12 years and over. The majority of trials that evaluated interventions to manage bladder and bowel health presented data for both male and female in a combined form making it impossible to estimate the effect of the intervention(s) on male participants only. In some cases, where the male data were presented separately, the population was too small to provide adequate power, and therefore most comparisons between treatment groups were found to have statistically insignificant differences in effectiveness.Conclusions: Implications for practice - There is little quantitative evidence for the effectiveness of interventions to improve men’s awareness of bladder and bowel health. Therefore few recommendations can be made. Pelvic floor muscle exercises with or without additional interventions such as biofeedback could be used to reduce the incidence of urinary incontinence in men who have had a prostatectomy. Education on lifestyle and behavioural modifications may be more effective in reducing lower urinary tract symptoms than doing nothing. Pelvic floor muscle exercises may be effective in treating post-micturition dribble in men with or without erectile dysfunction. Implications for research - With the exception of instruction of pelvic floor muscle exercises for men after prostatectomy, little quantitative research has been performed that establishes the effectiveness of interventions on men’s awareness of bladder and bowel health. While numerous interventions have been trialed on mixed gender populations, and these trials suggest that the interventions would be effective, their effectiveness on the male component cannot be definitively established. Therefore, well designed controlled trials using male sample populations only are needed to confirm these suppositions.